Telepsychiatry, access, and equity: accelerating mental health care for rural and low-income youth - Sharma, Mehek; Sharma, Vikram; Peeples, Dale (Frontiers in Public Health, 2025)
For rural youth, seeking mental health care often carries high stakes: in tight-knit communities where ‘everyone knows everyone,’ privacy is limited, and delays in mental health support can allow manageable symptoms to escalate into crises. Telepsychiatry provides confidential, flexible, and timely access, enabling youth to seek help early and receive support without delay. This perspective synthesizes current evidence on telepsychiatry’s benefits and challenges and highlights opportunities for growth through hybrid care models, policy reforms pertaining to payment parity and credentialing by proxy for provider licensing, digital equity initiatives, and community-based approaches for building literacy and trust, ensuring that all youth including neurodivergent persons from rural, inner-city, and low-income communities can access effective, urgent, and private mental health care.